Late recovery in cerebral fat embolism - Srikanth, KP (Medknow Publications & Media Pvt Ltd, 2014)
Fat embolism syndrome presenting primarily with cerebral manifestations is rarely reported. We report here two such patients who showed complete recovery following initial deterioration. The aim of these reports is to highlight that prolonged intensive care and good rehabilitation can lead to normal neurologic recovery despite poor clinical picture initially. The importance of adequate oxygenation to prevent secondary brain damage is emphasized during prolonged recovery.